Possible drug-nutrient interactions in hospitalized children and elderly (Research, Society and Development, 2020)
The nutrients present in a diet can affect the the medication effects. Likewise, the drug can interfere with the absorption of some nutrients or even the effect of another drug. The objective was to evaluate the possible drug/drug interactions and between drugs/nutrients in geriatric and pediatric inpatients. Descriptive and transversal study developed in the geriatric and pediatric sectors of a Teaching Hospital in Pernambuco, Pernambuco, Brazil. Data collection took place between March and May 2018. Data was collected by consulting medical records of 20 elderly (≥60 years old) and 20 children (